Computed Tomographic Assessment of Individual Paranasal Sinus Compartment and Nasal Conchal Bulla Involvement in 300 Cases of Equine Sinonasal Disease - Dixon, Padraic M.; Barnett, Tim P.; Morgan, Rhiannon E.; Reardon, Richard J. M. (Frontiers in Veterinary Science, 2020)
Background: Computed tomographic (CT) imaging has allowed new anatomical studies and detailed clinical imaging of the complex, overlapping equine sinonasal structures. Despite the widespread use of CT, no study has specifically identified which compartments are most commonly affected with sinus disorders. CT has also shown the presence of intercurrent, ipsilateral nasal disorders, especially infection of the nasal conchal bullae (NCB) in many cases of sinus disease, but the frequency of intercurrent NCB infections has not been reported. Objectives: To identify which sinus compartments are most commonly affected in horses with clinical sinus disorders and to record the prevalence of NCB involvement in such cases. Study Design: Retrospective examination of CT images of horses with confirmed unilateral sinus disease. Methods: The CT images of 300 horses, from three different equine hospitals with clinically confirmed sinus disease [mainly dental (53%) and primary sinusitis (25.7%)] were retrospectively examined to determine which sinus compartments and NCBs were affected. Results: The rostral, more dependent sinus compartments were most commonly involved, i.e., the rostral maxillary sinus in 284/300 (94.7% affected) and the ventral conchal sinus (87% affected). The caudal maxillary sinus (65.3%), dorsal conchal sinus (52.7%), frontal sinus (26%), ethmoidal sinus (32%) and sphenopalatine sinus (28.7%) were less commonly affected. There was infection or destruction of the ipsilateral NCBs in 56% of horses with sinus disorders, including the ventral NCBs in 42.3%, dorsal NCBs in 29% and both NCBs in 18% of cases. Main Limitations: The horses with sinonasal disease that underwent head CT imaging include more problematic cases and horses of high value, rather than the general horse population. Conclusions: The more dependant (i.e., the RMS and VCS) sinus compartments are most commonly involved in sinus disorders, with the RMS involved in nearly every case. The more dorsally located sinuses (i.e., caudal group) are less commonly involved. Many horses with sinus disease also have disorders of their nasal conchal bullae and so the term sinonasal disease seems appropriate for these disorders.